Instrumentation For The On-Stress Analysis Of Ash Content And Moisture Content In Coal Cleaning Plants - Gunter Fauth (Society for Mining, Metallurgy & Exploration, 1984)
The setting of tasks for the process control of coal cleaning, and in this connection the requirements for instrumentation can be classified into the following three fields: - Monitoring the operation of individual units, or process steps, - Control of units or process steps, - Control of the entire coal cleaning process with the intention of optimizing the operation and the profitability of the process. Instrumentation is affected by the type of cleaning processes. For introduction Figure 1 shows the simplified flow sheet of coal preparation which is usual in the German Ruhr District and in which desirable places for the measurement of ash, moisture and sulfur content are marked. The preparation plant is supplied with run-of-mine coal from the shaft via a homogenization facility. In a first step of primary classifying the raw feed coal is screened at about 10 mm. The raw coarse coal ( = 10 mm) is sorted by jig washers or heavy-medium separators. the raw fine coal (< 10 mm) at first is pneumatically sized at about 0.5 to 0.75 mm. The fines, the aspirated dust, are a finished partial product which will be added to the final metallurgical or steam coal. The material 10 to 0.75 mm subsequently is sorted in fine coal jigs and dewatered in centrifuges. The sludge obtained with the wet cleaning processes is dewatered in thickeners and fed to the flotation. Concentrate and tailings are dewatered by filters or bowl centrifuges and by chamber filter presses or belt filter presses, respectively. The partial products coarse coal, fine coal, flotation concentrate, aspirated dust, and middlings are blended to result in the sellable products metallurgical and steam coal.